Clinical phenomenology of fibromyalgia syndrome in male patients: same but different - Drusko, Armin; Renz, Malika; Schmidt, Hannah; Schlömp, Lea; Papaiannou, Vassilios; Schmidt, Norbert; Tost, Heike; Treede, Rolf-Detlef; Eich, Wolfgang; Tesarz, Jonas (The journal of pain, 2023)
The majority of knowledge about fibromyalgia syndrome (FMS) derives from studies of female patients. Little is known about the clinical characteristics and treatment outcomes of male patients with FMS. In this retrospective cohort study with a prospective posttreatment follow-up, we investigated whether male patients with FMS differ from female patients in terms of 1) symptom burden, 2) psychological characteristics, and 3) clinical treatment response. We identified 263 male (4%) out of 5,541 patients with FMS completing a 3-week multimodal pain-treatment program. Male patients (51.3 ± 9.1 years) were age- and time-matched (1:4) with female patients (N = 1,052, 51.3 ± 9.0 years). Data on clinical characteristics, psychological comorbidities, and treatment responses were obtained from medical records and validated questionnaires. Levels of perceived pain, psychological comorbidity, and functional capacity were similar between genders, although male patients with FMS showed a higher prevalence of alcohol abuse. Compared to female patients, male patients experienced themselves less often as overly accommodating (Cohen’s d = −.42) but more often as self-sacrificing (d = .26) or intrusive (d = .23). Regarding pain coping, male patients were less likely to utilize mental distraction, rest- and relaxation techniques, or counteractive activities (d = .18-.27). Male patients showed a slightly worse overall response rate than women (69% vs 77%), although differences between individual outcome measures were small (d < .2). Although male and female patients in our cohort were similar in clinical presentation and treatment response, the gender-specific differences in interpersonal problems and pain coping suggest consideration of these aspects in the treatment of male patients with FMS. - Perspective - Knowledge about fibromyalgia mostly derives from studies of female patients. Identifying and understanding gender-specific differences in fibromyalgia is an important roadmap in the treatment of this syndrome by focusing on specific gender aspects such as differences in interpersonal problems and pain coping mechanisms.